Maqāṣid, Maṣlaḥa, and Legal Pluralism: Islamic Law’s Governance of Adolescent Marriage After Premarital Pregnancy - Bakence, Lutfi; Sultan, Lomba; HL, Rahmatiah; Ridwan, Saleh (PT. Riset Press International, 2025)
Premarital pregnancy continues to drive adolescent marriage in Indonesia where religious, customary, and state norms intersect. This study examines how marriages following premarital pregnancy are governed in North Halmahera and identifies the conditions under which negotiated compromises protect or harm young families. Using a qualitative case study, we conducted in-depth interviews with clerics, customary leaders, officials, adolescents, and parents, observed community proceedings, and analyzed local documents; thematic and cross-case analysis with triangulation and reflexivity ensured credibility and ethical safeguards. Cases cluster among adolescents aged fifteen to nineteen with incomplete schooling and financial strain, and decision windows compress rapidly once pregnancy becomes known. Proximal and structural drivers include gaps in sexuality education, limited parent–child communication, peer and media influence, low practical religious literacy, and poverty. Three honor-restoring mechanisms recur: swift marriage, customary acknowledgment through penebusan, and judicial dispensation. Outcomes diverge: when safeguards for consent, psychosocial readiness, maternal and child health, continued education, and civil documentation are embedded, reintegration improves; when compromises focus on ritual display alone, risks accumulate and legal identity gaps persist. The analysis refines legal pluralism in practice by showing how maqasid- and maslaha-oriented reasoning legitimates harm-reduction pathways and explains subdistrict variation by leader networks and administrative capacity. The study offers a micro-process model and recommends locally coherent sexuality education, culturally anchored premarital counseling, integrated referral systems, clear documentation routes, and measured use of dispensation.